Answer:
Step-by-step explanation:
Given : Expression =
Simplifying the expression :
Step 1. Write the expression =
Step 2. Add the similar elements:
=
Step 3. Add the similar elements:
=
Therefore, is the simplified form of
Answer:
y = 6
Step-by-step explanation:
Given that y varies directly with x then the equation relating them is
y = kx ← k is the constant of variation
To find k use the condition y = 3 when x = 9, then
k = = = , thus
y = x ← equation of variation
When x = 18, then
y = × 18 = = 6
Answer:
give my about ten mins i got to finish this final exam for math seg 1
Step-by-step explanation:
The change of base formula allows you to write a logarithm in terms of logarithms with another base. It follows this pattern,
where a≠1 and b≠1
Assigning the base to be 7,
I hope I was able to answer your question. Have a good day.